Karakteristik Organoleptik Brownis Berbahan Tepung Komposit Terigu dan Ubi Jalar Kuning - Ghaffar, Mufti; Nurhamzah, Lutfi Yulmiftiyanto (Universitas Bumigora, 2024)
Brownis are a cake product that is widely consumed by the public, and is prepared traditionally. Brownis tend to contain unbalanced nutrients. So it is considered a food that has little health benefits. One way to increase the nutritional value of Brownis is to substitute other ingredients that have complete nutritional content, namely yellow sweet potato flour. It is known that yellow sweet potatoes contain carbohydrates, minerals, antioxidants and fiber. This research aims to determine the effect of the percentage of yellow sweet potato on organoleptic test results in terms of color, aroma, taste, texture and appearance. The method used is the hedonic test to determine the level of preference and the best formulation. The hedonic scale uses a score of 1: dislike very much, 2: dislike, 3: neutral, 4: like, and 5: like very much. Formulation of brownie products with substitution percentages for yellow sweet potato, namely 0%, 25% and 50%. Based on the research results, the 25% yellow sweet potato flour substitution formulation was the product most preferred by panelists based on the hedonic value of taste, texture, appearance and color. So it can be concluded that the brownie product with the addition of 25% yellow sweet potato is the best formulation in this study. This research contributes to providing practical solutions to improve the nutritional value of brownis products.